CaMKII regulation of cardiac ryanodine receptors and inositol triphosphate receptors - Camors, Emmanuel; Valdivia, Héctor H. (Frontiers in Pharmacology, 2014)
Ryanodine receptors (RyRs) and inositol triphosphate receptors (InsP3Rs) are structurally related intracellular calcium release channels that participate in multiple primary or secondary amplified Ca2+ signals, triggering muscle contraction and oscillatory Ca2+ waves, or activating transcription factors. In the heart, RyRs play an indisputable role in the process of excitation-contraction coupling as the main pathway for Ca2+ release from sarcoplasmic reticulum (SR), and a less prominent role in the process of excitation-transcription coupling. Conversely, InsP3Rs are believed to contribute in subtle ways, only, to contraction of the heart, and in more important ways to regulation of transcription factors. Because uncontrolled activity of either RyRs or InsP3Rs may elicit life-threatening arrhythmogenic and/or remodeling Ca2+ signals, regulation of their activity is of paramount importance for normal cardiac function. Due to their structural similarity, many regulatory factors, accessory proteins, and posttranslational processes are equivalent for RyRs and InsP3Rs. Here we discuss regulation of RyRs and InsP3Rs by CaMKII phosphorylation, but touch on other kinases whenever appropriate. CaMKII is emerging as a powerful modulator of RyR and InsP3R activity but interestingly, some of the complexities and controversies surrounding phosphorylation of RyRs also apply to InsP3Rs, and a clear-cut effect of CaMKII on either channel eludes investigators for now. Nevertheless, some effects of CaMKII on global cellular activity, such as SR Ca2+ leak or force-frequency potentiation, appear clear now, and this constrains the limits of the controversies and permits a more tractable approach to elucidate the effects of phosphorylation at the single channel level.